Increasing the Growth and Production of Pakcoy Plants (Brassica rapa L.) with Variations in Planting Media in Hydroponic Systems - Rovel Lando Fambari; Jonni; Chairunnisak; Sari Rukmana Okta Sagita Chan; Eka Susila; Benny Satria Achmad (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2026)
Pakcoy (Brassica rapa L.) is a short-lived leafy vegetable with high nutrient requirements and is highly responsive to environmental conditions, making it well-suited for cultivation using hydroponic systems. Additionally, the limited availability of agricultural land in urban areas due to land conversion necessitates efficient cultivation methods that do not rely on soil. Hydroponic systems offer more precise control over nutrient management and the growing environment compared to conventional soil-based cultivation, potentially increasing production efficiency on limited land. The success of hydroponic pakcoy production is significantly influenced by the type of growing medium, which supports root development, maintains water availability, and facilitates aeration and nutrient absorption. Therefore, research on various growing media is essential to identify the most effective medium for enhancing pakcoy plant growth and yield. This study aims to: 1) determine the effect of various growing media on the growth and production of pakcoy plants in hydroponic systems (Brassica rapa L.); and 2) identify the best alternative growing medium for optimizing the growth and production of pakcoy in hydroponic cultivation. The research was conducted from May to July 2025 in the greenhouse of the Payakumbuh State Agricultural Polytechnic, Harau District, Lima Puluh Kota Regency, West Sumatra. This study employed a completely randomized design (CRD) with a non-factorial approach. The factor studied was the growing media, consisting of seven treatments: rockwool, bamboo humus, coconut fiber, chopped fern, rockwool + bamboo humus, rockwool + coconut fiber, and rockwool + chopped fern. The parameters observed included plant height, number of leaves, leaf width, leaf length, root length, and fresh plant weight. The results indicated that variations in growing media significantly affected the growth and production of Pakcoy plants in the hydroponic system. The combination of rockwool and coconut fiber as planting media yielded the best results for Pakcoy plant growth and production. Therefore, the optimal alternative planting media for Pakcoy growth and production in the hydroponic system was rockwool combined with coconut fiber.